Використання різографії як найбільш поширеної технології цифрового трафаретного друку - Пономарьова, О. В. (ХНУРЕ, 2021)
Risography is the brand name of the method of rotary screen printing, which uses a printing plate made by burning micro-holes in the molding material to form printing elements. With the help of a risograph, high -quality printing products are obtained in large quantities. Sponsored letters, forms, business cards and other printed products are printed on it. The main advantages of modern risography are productivity, economy, reliability, environmental friendliness and others.
Keywords: різографія; трафаретний друк